The structure of concentrated Li-ammonia solutions as derived from MD simulations - Hannongbua, S.; Remsungnen, T.; Kiselev, M.; Heinzinger, K. (Condensed Matter Physics, 2003)
The results of Molecular Dynamics simulations of lithium-ammonia solutions
over the whole concentration range from 0.5 to 19.6 MPM at 240 K
are reported. The pseudopotential theory is employed at the higher concentrations
and the direct contribution to the total potential which has been
derived from ab initio calculations has been supplemented by three-body
terms. The resulting partial structure and radial distribution functions are
compared in detail with recent X-ray and neutron diffraction studies with
isotopic substitution. There is an overall good agreement between simulation
and experiment. Differences are discussed. The solvation number of
the lithium ion is found to be six for the dilute solution and four for the higher
concentrations in analogy to the hydration of Li⁺ found for various aqueous
solutions. В даній роботі представлені результати, отримані методом молекулярної динаміки для розчинів літій-аміакy для усього діапазону концентрацій від 0.5 до 19.6 MPM при температурі 240 К. Використовується теорія псевдопотенціалів при вищих концентраціях. Прямий
внесок загального потенціалу, який отримується з ab initio розрахунків, доповнюється тричастинковим доданком. Результуюча частинна структура і радіальні функції розподілу детально порівнюються
з рентгенівським і нейтронним розсіюванням з ізотопним заміщенням. Результати експерименту і моделювання добре узгоджуються.
Знайдено сольватаційні числа іонів літію для розведених розчинів
(шість), а також для розчинів з вищою концентрацією (чотири) по
аналогії з гідратацією іонів літію у різних водних розчинах.